Discussing citizenship with military policemen from Paraíba - Corrêa, Rosália do Socorro da Silva (2012)
This article presents the results of the pilot research carried out in the Military Police of Paraíba -PM-PB, 2005, in which we tried to understand the perception of 30 military policemen and officers about citizenship in the institution and in the internal relations between superiors and subordinates. The policemen who were interviewed belong to the Shock Squad and the 23rd Company, who work in ostensive policing. The selection of these units is justified by their locations in the capital and their distinct missions, characteristics that bring them closer to the proposed research object, for the doctorate, directed at the study of hierarchical relations in units of the Military Police of Pará-PM-PA, located in the capital and that perform different missions. The results showed that the intramural relationships in the PM-PB are undergoing changes, based on the concept of citizenship, trying to break with the old patterns of conduct that have always led them and still persist, despite the obstinate internal mobilization to overcome them.